2014
DOI: 10.1210/jc.2014-1367
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Irisin in Healthy, Young Individuals: Day-Night Rhythm, Effects of Food Intake and Exercise, and Associations With Gender, Physical Activity, Diet, and Body Composition

Abstract: In healthy, young individuals, circulating irisin displays a day-night rhythm, is correlated with lean body mass, and increases acutely after exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
154
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(194 citation statements)
references
References 27 publications
15
154
3
5
Order By: Relevance
“…Also, the browning formation that Irisin may cause could lead to reduced weight gain, up-regulated insulin sensitivity, reduced risk of diabetes type II and other metabolic disorders as animal studies indicate [89][90][91][92][93] , as well as increase daily resting energy expenditure in humans 94,95 . However, the secondary outcomes of our systematic review shows that even when Irisin was measured with the same ELISA (PP, EK-067-52) there was no relationship 22 or a positive relationship with resting energy expenditure 37 , and no association 72 or a positive association with BMI 71 . This specific ELISA kit (PP, EK-067-52) has been tested by a previous study for validity 27 , which showed it to be invalid for circulating Irisin identification.…”
Section: Quality Of Evidence and Limitationsmentioning
confidence: 77%
See 1 more Smart Citation
“…Also, the browning formation that Irisin may cause could lead to reduced weight gain, up-regulated insulin sensitivity, reduced risk of diabetes type II and other metabolic disorders as animal studies indicate [89][90][91][92][93] , as well as increase daily resting energy expenditure in humans 94,95 . However, the secondary outcomes of our systematic review shows that even when Irisin was measured with the same ELISA (PP, EK-067-52) there was no relationship 22 or a positive relationship with resting energy expenditure 37 , and no association 72 or a positive association with BMI 71 . This specific ELISA kit (PP, EK-067-52) has been tested by a previous study for validity 27 , which showed it to be invalid for circulating Irisin identification.…”
Section: Quality Of Evidence and Limitationsmentioning
confidence: 77%
“…This specific ELISA kit (PP, EK-067-52) has been tested by a previous study for validity 27 , which showed it to be invalid for circulating Irisin identification. Furthermore, Irisin measured with ELISA from the same manufacturer (Phoenix Pharmaceuticals) showed either no relationship 72 or a positive relationship with waist circumference 49 . This evidence shows inconsistent results of the relationship of Irisin with indices indicating the therapeutic role of the protein, even though the Irisin identification methods that used were identical.…”
Section: Quality Of Evidence and Limitationsmentioning
confidence: 95%
“…found that circulating irisin has a day-night variation with the lowest levels at 6:00 a.m. and the highest ones at 9:00 p.m. However, the blood collection was performed consistently at the same time of the day for individual participants (16). The minimum detectable level was 27.85 ng/mL.…”
Section: Determination Of Circulating Irisin and Other Biochemical Mementioning
confidence: 96%
“…However, there are discrepancies regarding the relation of irisin especially with obesity and T2DM. In some studies, a positive association was detected between irisin levels and BMI (24,25,26), while others reported null (27,28).In agreement with Tanisawa et al (29) showed that the Gallele of rs3480 was associated with increased insulin resistance and its complications. In contrast to our results, Nasser M et al ., (30) reported that The rs3480 GG associates with decreased risk of obesity (p = 0.005; odds ratio: 0.48) and lower body mass index (BMI).while rs1746661 variant is associated with elevated triglycerides.…”
Section: Discussionmentioning
confidence: 53%